PERIPROSTHETIC FRACTURE OF THE KNEE - Thành Toàn, Võ (Journal of Health and Aging, 2025)
Periprosthetic fractures around the knee are serious complications following total knee arthroplasty, commonly occurring in elderly patients with poor bone quality. The most frequent fracture site is the supracondylar region of the femur, followed by the tibia and patella. Causes may include low-energy trauma, suboptimal surgical technique, or implant loosening. Diagnosis and treatment of periprosthetic fractures around the knee are challenging due to interference from the implant and compromised bone quality. Treatment may be conservative in non-displaced fractures or surgical in cases of displacement, implant loosening, or comminuted fractures. Surgical options include locked plating, retrograde intramedullary nailing, or revision arthroplasty using long-stem components. Fracture classifications by Lewis-Rorabeck and Su are helpful in guiding management. Tibial and patellar periprosthetic fractures may also occur and require careful preoperative planning to avoid complications. Postoperative complications such as non-union, infection, or soft tissue injury are common when not properly managed. Prevention through patient screening, improved surgical technique, and close postoperative monitoring plays a critical role in reducing fracture incidence. Successful treatment requires a multidisciplinary approach involving orthopedic surgery, rehabilitation, and management of comorbidities.